Implementasi Pendidikan Karakter Sebagai Upaya Membentuk Akhlak Santri Di Pondok Pesantren - Cipto Sudirman; Khotimah Suryani (Fakultas Agama Islam, 2026)
Character education is an important foundation in shaping the morals of the younger generation, especially in Islamic boarding schools whose primary mission is to produce individuals with noble character. This study aims to analyze the implementation of character education and the factors that influence the formation of the morals of students at the Bustanul Thullab Sukodadi Islamic Boarding School. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data analysis uses the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The results show that character education is implemented through the habituation of worship, teaching Islamic values, the exemplary behavior of ustadz and caregivers, and fostering social activities such as community service and yellow book recitation. This implementation has proven effective in shaping the character of students who are disciplined, honest, responsible, and have integrity. The success of the formation of the morals of students is also supported by a conducive Islamic boarding school environment and the commitment of caregivers in providing consistent guidance. Thus, character education at the Bustanul Thullab Islamic Boarding School is able to make a real contribution to the formation of the morals of students.